Progress and prospect of ecological risks of land use change - Cao, Congjie; Song, Wei (Frontiers in Environmental Science, 2022)
Ecological risks reflect the extent to which ecosystems are threatened by human activities and environmental changes. Changes in land use/land cover can have profound impacts on the regional ecological environment, such as land desertification, soil erosion, a sharp reduction in forest resources, and biodiversity loss. To objectively reveal the current research status, we conducted an econometric analysis of relevant research papers from 1991 to 2021, published in Web of Science. The results are as follows: (1) In the past 30 years, the number of publications in the field of ecological risks of land use change increased, and the period from 1991 to 2021 can be divided into three stages: the budding period from 1991 to 2008, the rising period from 2009 to 2015, and the high-yield period from 2016 to 2021. (2) Research in this field covered 104 countries or regions, mainly in Asia, the Americas, and Europe. The top three cited countries were the US, China, and the UK. (3) The high-frequency keywords of land use change in the field of ecological risks mainly included “land use”, “management”, “climate change”, and “risk & ecology”. Keywords frequently appeared in Tree Map, such as "dynamics", "framework", and "model", indicating the main research methods in this field. Based on the results, we suggest that for the future development of this research field, the evaluation method system should be improved and multidisciplinary research should be strengthened, ultimately exploring new ways to solve the current ecological problems.